Curcumin protects against fenvalerate-induced neurotoxicity in zebrafish (Danio rerio) larvae through inhibition of oxidative stress - Jiansheng Zhu; Mingtao Huang; Chunlan Liu; Jingyu Wang; Li Zou; Fan Yang; Renfei Zhu (Ecotoxicology and Environmental Safety, 2023)
Fenvalerate (FEN), a typical type II pyrethroid pesticide, is widely used in agriculture. FEN has been detected in the environment and human body. However, the neurotoxicity of FEN has not been well elucidated. This study aimed to explore the mechanisms underlying FEN-induced neurotoxicity using the zebrafish (Danio rerio) model. We also investigated whether curcumin (CUR), a polyphenol antioxidant that exhibits neuroprotective properties, can prevent FEN-induced neurotoxicity. Here, zebrafish embryos were exposed to 0, 3.5, 7 and 14 μg/L of FEN from 4 to 96 h post fertilization (hpf) and neurotoxicity was assessed. Our results showed that FEN decreased the survival rate, heart rate, body length and spontaneous movement, and increased malformation rate. FEN caused neurobehavioral alterations, including decreased swimming distance and velocity, movement time and clockwise rotation times. FEN also suppressed neurogenesis in transgenic HuC:egfp zebrafish, reduced cholinesterase activity and downregulated the expression of neurodevelopment related genes (elavl3, gfap, gap43 and mbp). In addition, FEN enhanced oxidative stress via excessive reactive oxygen species and antioxidant enzyme inhibition, then triggered apoptosis by upregulation of apoptotic genes (p53, bcl-2, bax and caspase 3). These adverse outcomes were alleviated by CUR, indicating that CUR mitigated FEN-induced neurotoxicity by inhibiting oxidative stress. Overall, this study revealed that CUR ameliorated FEN-induced neurotoxicity via its antioxidant, indicating a promising protection of CUR against environmental pollutant-induced developmental anomalies.